Titanium and titanium based alloy prepared by spark plasma sintering method for biomedical implant applications—a review. (20th January 2021) - Annur, Dhyah; Kartika, Ika; Supriadi, Sugeng; Suharno, Bambang
Abstract: Titanium has been widely used in biomedical implant applications due to its excellent mechanical properties and biocompatibility. However, manufacturing titanium was quite challenging due to the need for high temperature while having high reactivity. Therefore, spark plasma sintering (SPS) is proposed as an advance rapid sintering technique which allows the fabrication of bulk and porous titanium for biomedical application. This review aims to explore the recent status of titanium alloys prepared by the SPS method. There are two common approaches of titanium development by the SPS method, develop a bulk titanium alloy, or develop porous titanium. The development of titanium for biomedical implant application was done by improving biocompatibility alloy and repair some unsatisfactory mechanical properties. Some low toxicity of titanium alloys (Aluminum free and Vanadium free) had been studied such as Ti–Nb, Ti–Zr, Ti–Ag, Ti–Mg, Ti–Nb–Zr, Ti–Nb–Cu, Ti–Nb–Zr–Ta, etc. SPS was shown to increase the mechanical properties of titanium alloys. However, porous titanium alloys prepared by SPS had gained much attention since it may produce titanium with lower elastic modulus in such a short time. Low elastic modulus is preferable for implant material because it can reduce the risk of implant failure due to the stress-shielding effect. Besides mechanical properties, some corrosion resistance and the biocompatibility of titanium are also reviewed in this paper.